Methodology for radionuclides quantification through "in vitro" bioassay - Velasques de oliveira, S. M.; Juliào, L. M. Q. C.; Sousa, W. O.; Mesquita, S. A.; Santos, M. S. (Cellular and Molecular Biology, 2010)
In Brazil, the radionuclides used for therapy are: 131I, 153Sm, 90Y and 177Lu, both for routine or research protocols. The radionuclide activity excreted by patients may be quantified by bioassay analysis and constitutes a powerful tool for individual treatment planning. The Bioassay Laboratory (LBIOVT) of the Institute of Radiation Protection and Dosimetry (IRD) has equipments for gamma and beta spectroscopy. These systems are calibrated in energy and efficiency using reference sources supplied by the National Laboratory of Radiation Metrology (LMNRI/IRD). The LBIOVT has operational procedures according ISO-ABNT-17025 recommendations and participates of international and national intercomparisons. The patient samples are collected immediately after radiopharmaceutical administrations, at the hospital or at the patient residence, and are handled, stored and transported according national radiation protection regulations. The radionuclide specific activity (Bq/L) is referenced to date and time of excretion, for the estimation of the individual biological half-live. The volume of excreta may carefully manipulated in order to avoid losses and misinterpretation in the activity quantification. The process of the LBIOVT accreditation and its participation in intercomparisons may guarantee the confidence of the results, allowing the minimization of the uncertainties in the individual monitoring.